2017
DOI: 10.3390/genes8120364
|View full text |Cite
|
Sign up to set email alerts
|

Delivery Mode and the Transition of Pioneering Gut-Microbiota Structure, Composition and Predicted Metabolic Function

Abstract: Cesarean (C-section) delivery, recently shown to cause excess weight gain in mice, perturbs human neonatal gut microbiota development due to the lack of natural mother-to-newborn transfer of microbes. Neonates excrete first the in-utero intestinal content (referred to as meconium) hours after birth, followed by intestinal contents reflective of extra-uterine exposure (referred to as transition stool) 2 to 3 days after birth. It is not clear when the effect of C-section on the neonatal gut microbiota emerges. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 51 publications
5
40
1
Order By: Relevance
“…Interestingly, development of enterocolitis was significantly associated with cesarean delivery at birth of the infant in the prospective HSCR patient cohort. Microbial composition in children delivered by cesarean section is known to be associated with skin commensals such as Staphylococcus , while the microbiome in children delivered by natural birth mode is characterized by vaginal bacteria, e.g., Bifidobacteria and Lactobacillus 107110 . However, since cesarean section was not a significant risk factor in the retrospective patient cohort, its role in enterocolitis development needs to be further examined.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, development of enterocolitis was significantly associated with cesarean delivery at birth of the infant in the prospective HSCR patient cohort. Microbial composition in children delivered by cesarean section is known to be associated with skin commensals such as Staphylococcus , while the microbiome in children delivered by natural birth mode is characterized by vaginal bacteria, e.g., Bifidobacteria and Lactobacillus 107110 . However, since cesarean section was not a significant risk factor in the retrospective patient cohort, its role in enterocolitis development needs to be further examined.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates delivered by pre-labor Cesarean section, on the other hand, miss out on this microbially-rich bath. High-throughput amplicon sequencing of bacterial DNA has shown that vaginally-delivered infants are colonized with organisms mainly from the mother's vaginal and intestinal microbiota, whereas Cesarean-delivered infants are colonized with skin and environmental microbiota [ 23 25 ]. Our findings are also consistent with other studies that have shown that compared to vaginally-delivered infants, Cesarean-delivered infants intestinal flora is characterized by a notable absence of Bifidobacterium spp .…”
Section: Discussionmentioning
confidence: 99%
“…Maternal transmission can influence microbiota richness and diversity. Infants born by birth canal compared with those born by caesarean section delivery show a greater microbial diversity [ 139 ]. Nursing as well as skin and oral contact with the mother influence maternal transmission.…”
Section: Gut Microbiota and Their Metabolites In Adenomatous Colonmentioning
confidence: 99%